SEARCHING FOR THE VALUE OF SOCIAL SCIENCES AND HUMANITIES IN LITHUANIA: MONISM, PLURALISM AND ADMINISTRATIVE CONTROL - Kraniauskas, Liutauras; Gedutis, Aldis (Sociologija. Mintis ir veiksmas, 2016)
The article analyzes the evaluation discourse and practices of Lithuanian social sciences and humanities (SSH). The special attention is also paid at the ways, in which two rival philosophical conceptions of science – monism and pluralism – structure national field of science. The issues of recognition and identification of scientific value are discussed structurally reconstructing the major premises and approaches in the social sciences and humanities evaluation discourse from 1994 to 2015. The article as well reveals what social implications in academia the legal and administrative decisions generated by this discourse had, and what were the reactions to the decisions by the research communities in social science and humanities. We argue that the dynamics of the administrative system is generated not only by the tension between monism (positivism) and pluralism (epistemic variety) but also by resistance of research communities to increasing administrative control. The latter form of control employing its technical decisions implicitly devalues SSH and negates their meaningfulness. Administrative control orients towards global systems of symbolic prestige, which results in reproduction of unequal power relations between different research disciplines as well as between researchers and research administrators.